Family ownership, corporate governance and risk-taking - Luis Otero-González; Luis-Ignacio Rodríguez-Gil; Milagros Vivel-Búa; Aracely Tamayo-Herrera (Journal of Risk and Financial Management, 2022)
This paper analyses the effect of family ownership and the characteristics of the board of directors on the risk assumed by Spanish non-financial companies. The sample consists of 176 Spanish non-financial companies listed on Spanish stock exchanges during the period 2012-2015. The results show that the level of family ownership concentration affects the level of exposure to risk non-linearly and confirms the importance of the characteristics of the board of directors in risk-taking.
Keywords: 330; family ownership; risk-taking; corporate governance